The heat supply object thermal regime under conditions of gas infrared emitter and air exchange system joint operation; Journal of Physics: Conference Series; Vol. 2119 : The XXXVII Siberian Thermophysical Seminar (STS37) 2021 - Kuznetsov G. V. Geny Vladimirovich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna; Vyatkin A. V. Aleksandr Vitaljevich (2021, 2021)
Title screen